Interference to the Secondary Cable Caused by a Very Fast Transient Overvoltage in a Gas-Insulated Switchgear Substation. (23rd March 2022) - Lin, Hanliang; Zhang, Zhiyuan; Liu, Hongshun; Wang, Yifan; Liu, Yingnan; Yu, Dayang
Abstract : When a very fast transient overvoltage (VFTO) propagates in a high-voltage bus, the capacitive voltage transformer (CVT) causes considerable interference on its secondary side, which will affect the normal operation of the secondary equipment. In this article, a CVT equivalent calculation circuit model was established, and the disturbance voltage of the secondary cable was deduced and calculated. Using electromagnetic transient simulation software, a simulation model of the secondary cable disturbance caused by the VFTO in a 500 kV gas-insulated switchgear (GIS) substation was established, the disturbance voltage at the end of the secondary cable was simulated and analyzed, and the effects of the length of the secondary cable and the grounding mode of the shield on the disturbance were studied. Combined anti-interference measures are also suggested, which use a spiral tube damping busbar, grounding at both ends of the shield using multistrand conductors and installing filter capacitors, all of which greatly reduce the amplitude and harmonic components of the disturbance voltage of the secondary cable.